Patient Safety without Patient Advocacy is improbable, as they are synonymous. Is there a Theory-Practice-Ethics gap? - Mortell, manfred (Nova science publishers, 2020)
The aim of a culture of safety in healthcare is to reduce and/or eliminate the risk of harm to patients. However, despite a universal stance towards patient safety, since the Institute of Medicine’s landmark report of 2000, “To Err is Human, building a safer health system” there remains a disturbing escalation in the healthcare errors among hospitalized patients. This underscores trepidations about healthcare professionals and providers’aptitude as effective and caring patient advocates to provide high quality, safe care. In the context of these healthcare mistakes, the “Theory-Practice gap” is often cited as an offending perpetrator. Within this exemplar, there is often a disparity between theoretical knowledge and its application in practice. Evidence relating to the non-integration of theory and practice makes the assumption, that educational dynamics may affect learning and practice outcomes and hence, the “Gap”. Whatever you call them, healthcare mistakes, medical errors, faults, or miscalculations. This exemplar, acknowledges that healthcare professionals and providers are provided with theoretical knowledge and prepared with skills to practice competently and safely. Yet, these same healthcare professionals and providers continue to be noncompliant with the recommended evidence-based practices which creates an ethical dilemma. Therefore, to bridge the gap between theory and practice, a “Theory-Practice-Ethics gap” must be considered when appraising the unacceptable outcomes in healthcare practices, and the failure of healthcare professionals and providers to fulfil their moral duty of care, as patient advocates. One of the defining characteristics of a patient advocate is to ensure patient safety. By convention, patient advocacy is an integral philosophy in healthcare, and an obligation which is expected to be fulfilled by healthcare professionals and providers in the course of discharging their duties. Primum non nocere ‘above all, do no harm’ is a fundamental concept within the healthcare model. However, there is evidence of a failure to implement of this moral concept which relates to a patient’s safety and the advocacy role expected from healthcare professionals. Healthcare professionals declare that this is because of the ambiguity associated with the comprehension of the advocacy concept in relation to the safety role. In addition to the challenge of role acceptance within a patient safety forum as a misunderstood and unappreciated responsibility. The analytical exploration of patient advocacy related to patient safety and the concept of a “Theory-Practice-Ethics gap” will be presented within this chapter, to reinforce the importance of their synonymous relationship for trustworthy healthcare practices. Healthcare professionals and providers need to be mindful of the importance of patient advocacy and the utilization of a safety science which leads to a higher quality of safe patient care.